2003
DOI: 10.1007/s00374-003-0680-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the identification and enumeration of microorganisms with potential for suppressing fungal plant pathogens

Abstract: This paper describes a method that allowed counting of both the total culturable and antagonistic microorganisms in a given source such as compost. Fusarium solani, used as the test fungus, was spreadplated on quarter-strength (1/4) potato dextrose agar (PDA), its surface was exposed in a laminar flow for 4 h and then another layer (2-3 mm thick) of 1/4 PDA was poured over it, on which an appropriate dilution of a compost sample was spread-plated. Microorganisms in the compost samples appeared first, and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…'Panchagavya' (PG; Sanskrit for a blend of 'five products from cow') is a traditional product prepared in India by fermenting cow dung, cow urine, milk, curd and clarified butter (ghee) [1]. BD500, a biodynamic preparation that is also called as horn manure and 'Cow pat pit' (CPP) are preparations from cow dung that are used in organic farming [2,3]. Biodynamic products are included in the list of materials and techniques permitted in organic farming by an EC regulation (834/2007).…”
Section: Introductionmentioning
confidence: 99%
“…'Panchagavya' (PG; Sanskrit for a blend of 'five products from cow') is a traditional product prepared in India by fermenting cow dung, cow urine, milk, curd and clarified butter (ghee) [1]. BD500, a biodynamic preparation that is also called as horn manure and 'Cow pat pit' (CPP) are preparations from cow dung that are used in organic farming [2,3]. Biodynamic products are included in the list of materials and techniques permitted in organic farming by an EC regulation (834/2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many biodynamic preparations obtained from cow dung have shown antagonistic effect against plant pathogens such as Rhizoctonia bataticola (Rupela et al 2003;Somasundaram et al 2007;Radha and Rao 2014). An investigation by Mary et al (1986) revealed cow dung extract to be more effective than antibiotics like Penicillin, Paushamycin and Streptomycin in controlling bacterial blight of rice.…”
Section: Agriculture Managementmentioning
confidence: 99%
“…To be an effective PGPR, bacteria must be able to colonize roots because bacteria need to establish itself in the rhizosphere at population densities sufficient to produce the beneficial effects. The exact mechanism by which PGPR stimulate plant growth is not clearly estimated, although several hypothesis such as production of phytohormones, activation of phosphate solubilization and promotion of the mineral nutrient uptake are usually believed to be involved (Rupela and Kumar, 1999).…”
Section: Resultsmentioning
confidence: 99%